PROGNOSTIC VALUE OF THE FRAILTY SCALE FOR MORTALITY IN ELDERLY PATIENTS ADMITTED TO THE TOXICOLOGY INTENSIVE CARE UNIT. (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the prognostic value of the Clinical Frailty Scale (CFS) for mortality in elderly patients admitted to the Toxicology Intensive Care Unit (ICU).Subjects and Methods: This was a prospective observational cohort study with longitudinal follow-up on 95 patients aged ≥60 years who were hospitalized in the ICU of Thong Nhat Hospital from January 1, 2025 to June 30, 2025. Frailty was assessed 2 weeks prior to hospitalization through interviews with family members. A patient was considered frail when the CFS score was ≥5. Treatment outcomes were divided into two groups: survival and death.Results: The mean age was 76.7 years, and males accounted for 51.6%. The prevalence of frailty was 84.2%. A Charlson Comorbidity Index (CCI) >7 was found in 15.8% of patients. The most common comorbidities were hypertension (82.1%) and diabetes mellitus (42.1%). The ICU mortality rate was 57.9%. Two factors were significantly associated with in-hospital mortality: frailty (OR 2.33; 95% CI 1.95–8.79; p
Keywords: Clinical Frailty Scale, Toxicology Intensive Care Unit, Mortality Rate